Ionospheric responses during equinox and solstice periods over Turkey - Karatay, Secil; Cinar, Ali; Arikan, Feza (Elsevier BV, 2017)
Abstract Ionospheric electron density is the determining variable for investigation of the spatial and temporal variations in the ionosphere. Total Electron Content (TEC) is the integral of the electron density along a ray path that indicates the total variability through the ionosphere. Global Positioning System (GPS) recordings can be utilized to estimate the TEC, thus GPS proves itself as a useful tool in monitoring the total variability of electron distribution within the ionosphere. This study focuses on the analysis of the variations of ionosphere over Turkey that can be grouped into anomalies during equinox and solstice periods using TEC estimates obtained by a regional GPS network. It is observed that noon time depletions in TEC distributions predominantly occur in winter for minimum Sun Spots Numbers (SSN) in the central regions of Turkey which also exhibit high variability due to midlatitude winter anomaly. TEC values and ionospheric variations at solstice periods demonstrate significant enhancements compared to those at equinox periods.
Keywords: 13. Climate action